A Study of Hearing Loss of Chain Saw Workers - Toriyama, Minoru (AUDIOLOGY JAPAN, 1977)
Otolaryngological and audiological examinations were done on the chain saw workers, and eighty seven subjects out of one hundred three workers were studied. No ear infections or hearing loss in past history were detected. The average hearing thresholds for 250, 500, 1, 000, 2, 000, 4, 000, 8, 000Hz in each decade were calculated by using a computer process. There were no remarkable differences of hearing loss in the lower frequencies than 2, 000Hz in each decade, but there were difference more than 20dB in 4, 000 and 8, 000Hz between the second and fifth decades. There were no significant difference according to the years of their experiences. It might be said that the hearing loss of the chain saw workers increased in accordance with the age, and their hearing loss were always worse than that of those working in office, but was better than that of those working in the noisy iron manufacturing industry. A typical pure tone audiogram for the chain saw workers was not a c-5 dip type, but a c-6 injured type. The hearing loss was found in fourteen percents in the second decade, twenty in the third, twenty two in the fourth, and thirty two percents in the fifth.